Teologiczna ocena prośby o obcą interwencję przeciw rodakom w 1 Mch 6,21-27 - Nawrot, Janusz (Poznańskie Studia Teologiczne, 2017)
The passage 1 Macc 6: 21-27 contains no less than a request of renegades from the Jewish community for military intervention of the Seleucid troops in Judea. This request serves to end the Maccabean Revolt and continue with the policy of transforming Israel into a region completely submitted to the central royal authority. As such, and from a theological point of view, the renegades’ request receives a completely negative evaluation from the inspired author. The question why the citadel’s besieged defenders even manage to escape and do it successfully is given here much thought. If God is in one way or another the foundation and cause of all human activity in the theology of the Old Testament, then the successful escape could be evaluated as God’s objection to the arbitrary actions taken by Judas, who becomes too intoxicated with his previous achievements. The siege of the citadel might be perceived as the insurgents’ insubordination to God’s will and consequently a beginning of His withdrawal from supporting the rebels, which ultimately ends in their defeat in the soon-to-come Battle of Elasa.